The principles of medical ethics and medical research Os princípios da ética médica e da pesquisa médica - John Harris (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
In this paper I discuss the application of the principles of medical ethics and of medical research to the case of children and others whose consent to treatment and to research is problematic. Public health depends substantially on the possibility of ongoing research into all conditions which affect the health of the people. Constraints on this research are therefore a public health issue. Moreover and more importantly the possibility of predictive testing and indeed of screening for health-relevant conditions is an important public health tool, and limitations on the use of this tool are of great significance to public health medicine. Having considered the particular problems created by research and predictive testing on children for late-onset conditions I go on to discuss research on those whose consent is problematic more generally. I conclude with radical recommendations for the reform of The Declaration of Helsinki and of the International Ethics Guidelines for Biomedical Research Involving Human Subjects, prepared by the Council for International Organizations of Medical Sciences (CIOMS). Nesse artigo, discuto a aplicação dos princípios de ética médica e da pesquisa médica ao caso de crianças e outros cujo consentimento a tratamento e pesquisa é problemático. A saúde pública depende substancialmente da possibilidade da continuidade de pesquisas dirigidas a todas as condições que afetam a saúde da população. Restrições nessas pesquisas são, portanto, uma questão de saúde pública. Além disso, e mais importante, testagens preditivas e, especialmente, screening para condições relevantes (para) à saúde constituem-se em valiosos instrumentos de saúde pública. Limitações no uso desses instrumentos são da maior significância à medicina ligada à saúde pública. Levando em consideração os problemas particulares criados pela pesquisa e testagem preditiva para crianças no que se refere a condições que se manifestam tardiamente, prossigo discutindo investigações naqueles cujo consentimento é problemático em termos mais gerais. Concluo com recomendações radicais para a reforma da Declaração de Helsinki e das Orientações Éticas Internacionais para Pesquisa Biomédica Envolvendo Sujeitos Humanos, preparadas pelo Council for International Organizations of Medical Sciences (CIOMS).